The Prevalence characteristics and related factors of workplace violence in healthcare workers in emergency departments of government hospitals in region 6 health provider. - พชรธนสาร นภัสวรรณ; เลิศมหาฤทธิ์ สมรัตน์ (Journal of Preventive Medicine Association of Thailand, 2018)
The purpose of this study was to study prevalence, characteristics and related factors of workplace violence among healthcare workers in accident and emergency departments of government hospitals in Region 6 Health Provider. This study was a crosssectional study. Self-reported questionnaires were completed by 472 participants during July to December 2017. The results revealed that the prevalence of workplace violence in the previous year was 61.7% (95% CI: 57.4% to 65.9%). The prevalence of verbal violence, physical violence and sexual violence were 94.2%, 26.1% and 6.5% respectively. Troublemakers who committed physical violence and sexual violence were patients while troublemakers who committed verbal violence were patients’ relatives. Related factors of physical violence were male, little work experience, auxiliary, working hours approximately more than 48 hours per week and lack of staff (p-value<0.05). Related factors of verbal violence were young age, little work experience, holding a position as an operator, direct interaction with patients and patients’ relatives, shift work and working hours approximately more than 48 hours per week (p-value<0.05). Workplace violence among emergency healthcare workers is frequent and affects both physical and mental health of healthcare workers including causing burnout and early resignation. The study of prevalence and related factors of workplace violence will lead to planning for setting management and prevention guidelines and reducing the impact of workplace violence incidents more suitably and effectively.